Development of Ethnoscience-Based Science Education Module Using a Case Based Learning Model - Ketut Sri Kusuma Wardani; Fitri Puji Astria; Nurwahidah Nurwahidah (Jurnal Penelitian Pendidikan IPA, 2023)
This research is a research and development (R&D) study using the 4- D model. The research aims to produce valid a integrated ethnoscience science education module using a case based learning model. The data sources consisted of three expert validators who used validity instruments with four indicators (structure, organization of material, language, and appearance). The research data were analyzed using a quantitative descriptive method. Test the validity of the learning tool using score validation analysis. The results of the validity test show that the average score validation for structure module is 3.89 with a very valid category, for the material's organization it is 3.66 with a very valid category, for the language it is 3.67 with a very valid category, and for the appearance it is 3.73 with a very valid category. With a very valid category, the overall average mark validity is 3.74.